Navajo places : history, legend, landscape : a narrative of important places on and near the Navajo Reservation, with notes on their significance to Navajo culture and history - Linford, Laurance D. (University of Utah Press, 2000)
A place-name guide covering the entire traditional Navajo homeland includes some 1,200 entries appearing in alphabetical order by name and organized by state. Each entry includes the English name, elevation, county, meaning of the Navajo name, significance if known, description, and location. Also includes introductory material outlining Navajo history, culture, and ceremony.